ANALISIS NILAI KREATIVITAS PADA CERITA PENDEK DALAM BUKU BAHASA INDONESIA KELAS 2 KURIKULUM MERDEKA DI SEKOLAH DASAR - Syarifah Kurniawati; Fajriyatul Munawaroh; Nur Kholisa Aprilia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the value of creativity in short stories in Indonesian language books for grade 2 elementary schools. By using the literature review method, researchers can analyze short stories in Indonesian language books in the Merdeka curriculum. The results of this study can show that this book contains a short story and a poem. The existence of books containing stories is very popular with elementary school students because it can train illustrations and can increase their interests and talents. This creativity is highly regarded as a person's ability to use their imagination to get ideas or ideas through their interactions with others. Indonesian language textbooks containing short stories have a very important role in helping the development of students' creativity. Researchers found that this short story can be presented in a format that is quite concise, easy to understand, and in accordance with the profile of Pancasila students.